2004
DOI: 10.17221/5740-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of antibodies to chlamydophila abortus shown in awassi sheep and local goats in jordan

Abstract: ABSTRACT:A cold complement fixation test (CFT) was used to identify C. abortus infection in ewes and does in northern Jordan. Sera from 36 flocks of sheep and 20 flocks of goats were collected randomly. The results showed that 433 (21.8%) out of 1 984 ovine sera, and 82 (11.4%) out of 721 caprine sera, were seropositive for C. abortus infection, as indicated by a titre ≥ 1:40. However, all the tested sheep flocks and goat flocks (100%) revealed at least one seropositive animal. There was a strong association (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
21
2
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 19 publications
(17 reference statements)
5
21
2
1
Order By: Relevance
“…Our results showed that the risk of contracting Chlamydia increases significantly with the herd size. These results are in agreement with those of other studies, who observed that the prevalence of chlamydial infection was higher in herds with large numbers of animals (Al‐Qudah, Sharif, Raouf, Hailat, & AL‐Domy, ; Merdja et al., ). In general, larger herds might be expected to be associated with intensive management practices that are characteristically more difficult to control and let for closer contact between susceptible and infected animals.…”
Section: Discussionsupporting
confidence: 93%
“…Our results showed that the risk of contracting Chlamydia increases significantly with the herd size. These results are in agreement with those of other studies, who observed that the prevalence of chlamydial infection was higher in herds with large numbers of animals (Al‐Qudah, Sharif, Raouf, Hailat, & AL‐Domy, ; Merdja et al., ). In general, larger herds might be expected to be associated with intensive management practices that are characteristically more difficult to control and let for closer contact between susceptible and infected animals.…”
Section: Discussionsupporting
confidence: 93%
“…It has been shown that the reproductive organs of ewes and goats suffering from a latent infection can contain C. abortus even after more than 3 years after the infection (Morgan et al 1988). Lambs and kids delivered by infected animals are generally weak and die a few days after birth (Al-Qudah et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Titers below 32 were considered to be non-specific for C. abortus, although they also could have been the result of a mild C. abortus infection. Al-Qudah et al (2004) demonstrated that C. pecorum may be found in the intestines of some ovines without any pathological manifestation but with minimal antibody production compared to C. abortus. False positive results due to vaccination were not considered because the C. abortus vaccine is not available in Brazil.…”
Section: Discussionmentioning
confidence: 99%